2012
DOI: 10.17796/jcpd.37.2.261782tq73k4414x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Xylitol Consumption on Mutans Streptococci, Plaque and Caries Levels in Children

Abstract: Aim:The present study was designed to determine whether maternal xylitol consumption through regular chewing of xylitol gums can affect the salivary mutans streptococci (MS), dental caries, and dental plaque levels of their children. Method: Study sample included 60 mother and child pairs with high salivary mutans streptococcus (MS) levels. Samples were randomly divided into experimental group (30 pairs) and control group (30 pairs). Mothers in the experimental group received xylitol chewing gum treatment thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 1 publication
0
23
0
2
Order By: Relevance
“…An example of such an intervention was recommended in few studies. A recent study found that a maternal xylitol consumption by gum provided better preventive outcomes on salivary MS levels among there children, as compared with fluoride varnish treatments 16 . Another study concluded that this intervention should be targeted to women with high levels of MS counts 17 .…”
Section: Discussionmentioning
confidence: 99%
“…An example of such an intervention was recommended in few studies. A recent study found that a maternal xylitol consumption by gum provided better preventive outcomes on salivary MS levels among there children, as compared with fluoride varnish treatments 16 . Another study concluded that this intervention should be targeted to women with high levels of MS counts 17 .…”
Section: Discussionmentioning
confidence: 99%
“…We divided our data into multiple groups according to the time for follow‐up. The followed time in the first group ranged from 6 to 9 months, including Alamoudi et al . which provided data on children who were 6 months old, and Fontana et al .…”
Section: Resultsmentioning
confidence: 99%
“…which provided data only on children who were 9 months old, and we picked the data on children who were 9 months old in Nakai et al . The followed time in the second group ranged from 12 to 18 months, including Alamoudi et al ,. Nakai et al ,.…”
Section: Resultsmentioning
confidence: 99%
“…Alamoudi et al [12,13], studying mothers of 10-36-month-old children, which were using a chewing gum with 1.8 g of xylitol three times a day for 3 months, found no significant increase of S. mutans number in saliva, as well as no increase in the DMFT value in their children compared to the children of the mothers who were given a fluoride varnish. However, no difference in plaque in the children was found.…”
Section: Benefits Resulting From Xylitol Usementioning
confidence: 99%